Therapeutic advances in 5q-linked spinal muscular atrophy - Umbertina Conti Reed; Edmar Zanoteli (Arquivos de Neuro-Psiquiatria)
ABSTRACT Spinal muscular atrophy (SMA) is a severe and clinically-heterogeneous motor neuron disease caused, in most cases, by a homozygous mutation in the SMN1 gene. Regarding the age of onset and motor involvement, at least four distinct clinical phenotypes have been recognized. This clinical variability is, in part, related to the SMN2 copy number. By now, only supportive therapies have been available. However, promising specific therapies are currently being developed based on different mechanisms to increase the level of SMN protein; in particular, intrathecal antisense oligonucleotides that prevent the skipping of exon 7 during SMN2 transcription, and intravenous SMN1 insertion using viral vector. These therapeutic perspectives open a new era in the natural history of the disease. In this review, we intend to discuss the most recent and promising therapeutic strategies, with special consideration to the pathogenesis of the disease and the mechanisms of action of such therapies.